18‐3: Polarized Emission from Stretch‐Aligned Perovskite Nanorods‐Polymer Composites with High Stability. Issue 1 (30th May 2018) - He, Juan; Wang, Yanan; Chen, Hao; Towers, Andrew; Yuan, Peisen; Jiang, Zhang; Zhang, Caicai; Chen, Jiangshan; Gesquiere, Andre J.; Wu, Shin-Tson; Dong, Yajie
Abstract : We demonstrate low cost, highly luminescent and highly stable CsPbBr3 perovskite nanorods‐polymer composite films which can provide polarized narrow emission after macroscale stretch‐alignment. With polarization ratio 0.23 and narrow linewidth of 18 nm, these films promise to improve the optical efficiency of LCD and help with wide color gamut display.